MENINGKATKAN PRESTASI BELAJAR PKN KONSEP MENDESKRIPSIKAN PENGERTIAN ORGANISASI MELALUI PENERAPAN METODE SIMULASI PADA SISWA KELAS V SD NEGERI TRUKO 01 UPTD PENDIDIKAN KECAMATAN BRINGIN SEMESTER 2 TAHUN PELAJARAN 2015/2016 - Ibnu Hasyim (Universitas Ngudi Waluyo, 2020)
The focus of research is on teacher’s effort to improve student learning achievement in Civics learning using simulation method in order to improve student learning achievement that was previously known to not as expected yet. This research was conducted on 5th grade students of Truko 01 elementary school of UPTD Education in District Bringin at second Semester in 2015/2016. The design of research using Classroom Action Research plan which stars from making the action plan, carrying out the action in learning, observing, and reflecting the action. The results of the reflection are used to make decision. The research data obtained from field notes, observations notes, planning documentation, and writing results. The instrument of collection is observation guidelines, field notes, and documentation. Data is analyzed using qualitative techniques approach, including the stages of data reduction, data exposure, verification, and data conclusions. The test validity of the data carried is carried out to re-checking (triangulation) with a colleague and students. After completing this research, the author can conclude that the Simulation Method can improve student achievement on 5th grade students of Truko 01 elementary school of UPTD Education in Bringin District in Civics Education. The average value of the learning process of students in the first cycle was 59.6 with a 58% mastery learning. The acquisition of the average value of student learning outcomes in the second cycle, which is 75 and 100% mastery learning.